Fruit compounds affect male sexual success in the South American fruit fly, Anastrepha fraterculus (Diptera: Tephritidae) - Vera, María Teresa (2013)
Although exposure to plants has been shown to influence sexual behaviour in a number of phytophagous insect species, a relatively small number of fruit flies have been investigated in that respect. Here, we evaluated the effect of exposure to the pulp of guava and mango and to essential oils emanating from glands in the flavedo area of lemons on the mating success of Anastrepha fraterculus (Wiedemann) (Diptera: Tephritidae) males. We also evaluated different durations of exposure and the need for physical contact with the fruit. Results showed that exposure to guava increased the mating success of both wild and laboratory males relative to non-exposed males. In addition, exposed wild flies copulated earlier than non-exposed males. Physical contact with the fruit or ingestion of compounds was not a prerequisite for this phenomenon to occur, since just the exposure to volatiles resulted in a significant enhancement in mating success. Exposure to mango did not affect male sexual performance. In contrast, exposure to lemon for 1 day decreased mating success of males relative to unexposed males, whereas exposure for longer periods seemed to eliminate this effect resulting in comparable mating success rates between treated and untreated males. These results provide a better understanding of the sexual behaviour of this species and may also find application for its control.